Impact of Tributyltin (TBT) on Energy Metabolism and Redox Homeostasis in Blue Crab Callinectes sapidus - Leonardo Airton Ressel Simões; Rafaella Sanfelice Normann; Daniela Drosdowski; Bruna Selau; Marjoriane de Amaral; Alex Sander da Rosa Araujo; Anapaula Sommer Vinagre (Metabolites)
Background/Objectives: Tributyltin (TBT), a potent biocide used in antifouling paints, is highly toxic to aquatic environments, causing oxidative stress, endocrine dysfunction, and metabolic disorders in aquatic organisms, including crustaceans. The blue crab Callinectes sapidus is an economically and ecologically important species in several countries worldwide and is considered an invasive species in Europe. Methods: This study evaluated the effects of 7 days of exposure to environmentally relevant TBT concentrations (100 and 1000 ng.L−1) on the intermediary metabolism and oxidative balance of the blue crab Callinectes sapidus. After exposure, hemolymph samples were analyzed to determine glucose, lactate, total protein, and cholesterol levels. In tissue samples, concentrations of triglycerides, glycogen, total glutathione (GSH), reactive oxygen species (ROS), sulfhydryls, lipid peroxidation (LPO), and glutathione S-transferase (GST) activity were assessed. Results: In the hemolymph, glucose and lactate levels increased, while the total cholesterol, triglycerides, and total proteins decreased in all exposed groups. The GST activity increased in exposed tissues, while the total GSH and sulfhydryl content decreased. The ROS concentration increased in response to higher TBT concentrations. Conclusions: These findings highlight the toxicity of TBT and show that 7 days of exposure to environmentally relevant concentrations disrupts the metabolic homeostasis and oxidative balance in C. sapidus. Additionally, this study demonstrates that C. sapidus is sensitive to TBT exposure and has potential as a model species for ecotoxicological studies.